Whistleblowing System: An Analysis of Implementation Readiness at Private Universities in Palembang City - Leriza Desitama Anggraini; Faradillah Faradillah (Jurnal Ilmiah Akuntansi, 2023)
This research investigates the implementation of a whistleblowing system utilizing the Technology Acceptance Model (TAM). TAM incorporates two main variables—user perceptions of benefits (perceived usefulness) and user perceptions of ease of use (perceived ease of use)—in the context of information system implementation. The study explores dimensions of information technology, including Perceived Ease of Use, Perceived Usefulness, and Behavioral Intention to Use, applying a quantitative approach. The study's population comprises students from various majors across different private universities, with non-probability sampling employed. Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis, facilitated by Smart PLS software, serves as the methodological framework. Results reveal the positive and significant impact of Perceived Seriousness of Wrongdoing, Authentic Leadership, and Behavioral Attitude on Behavioral Intention to Whistleblow. Moreover, Perceived Seriousness of Wrongdoing, Social Norm, Perceived Ease of Use, and Perceived Usefulness influence Behavioral Attitude. Notably, Perceived Usefulness, Perceived Ease of Use, and Authentic Leadership did not exhibit a significant impact on Behavioral Attitude. These findings contribute to the understanding of factors influencing whistleblowing behavior, providing valuable insights for organizational and academic stakeholders.